Images of eschatology of Antanas Vivulskis’ (1877-1919) Saint Mary Apparition Chapel in Šiluva - Rudokas, Kastytis (Landscape Architecture and Art, 2025)
The aim of this article is to discuss, through the method of hermeneutic analysis, the nature of Christian eschatology as a observer’s choice in perceiving architectural objects and how this process expands the semantic meanings of an original architectural creation. These meanings may have been implied by the architect but not necessarily intentional. To explore this issue, the study focuses on the only surviving architectural work by the Lithuanian-Polish architect Antanas Vivulskis—the Chapel of the Apparition of the Blessed Virgin Mary in Šiluva (1903–1924)—and the visual solution from the Šiluva Pilgrimage Center’s communication campaign: the conceptual architectural work titled The Cube.